Exploring the Critical Risk Factors of Public-Private Partnership City Hospital Projects in Turkey - Doğan Erdem, Tuğba; BİRGÖNÜL, ZEYNEP; Bilgin, Gözde; Akçay, Emre Caner (MDPI, 2024)
Governments face challenges in delivering essential public services due to their limited funds. This has led to an increasing reliance on the Public-Private Partnership (PPP) model, an alternative financing model involving a long-term collaboration between the private and public sectors to provide public services. Turkey, as a developing country facing financial limitations, has embraced the PPP model to address urgent public needs. Over the past decade, the Turkish Government has extensively utilized the PPP model, particularly in executing city hospital projects. However, investors have faced challenges in project execution due to various risk factors. Therefore, the main objective of this study is to explore the critical risk factors associated with PPP city hospital projects in Turkey. In this context, a comprehensive literature review was conducted to identify potential risks related to PPP city hospital projects. A questionnaire survey was implemented to assess the probability of occurrence and the severity of the impact of these risk factors. The collected data underwent analysis to determine the priority of these risk factors. The findings revealed that the top five most critical risk factors in PPP city hospital projects in Turkey are "foreign exchange rate fluctuations", "inflation rate volatility", "high finance costs", "fiscal issues", and "economic crises". Conversely, "unavailability of equipment" was identified as the least significant risk factor. The insights gained from this research can offer valuable guidance for prospective investors interested in participating in PPP city hospital projects in Turkey and other developing countries with similar conditions.
Keywords: Assessment; City Hospital; PPP; Project; Risk